Rancang Bangun Sistem Pemantauan Lampu Lalu-Lintas Berbasis PLC-SCADA - Tugino (Institut Teknologi Nasional Yogyakarta, 2024)
Traffic accidents are caused by disruption to traffic lights. This study aims to design and implement a prototype traffic light monitoring system based on PLC-SCADA to improve safety and traffic management through the integration of Programmable Logic Controller (PLC) and Supervisory Control and Data Acquisition (SCADA). The system development method involves the design of hardware and software that are connected simultaneously to the traffic light infrastructure. Current sensors are used to detect traffic light damage, while the SCADA system allows remote monitoring and control of traffic lights. The advantage of this system is that it can detect and respond quickly to traffic light damage so that repairs can be made immediately. The results of the study have shown that the prototype has worked well according to the desired design. The results of this study are expected to contribute to innovation in traffic light technology and provide benefits in improving traffic management and reducing accidents due to traffic light damage